Limited Specificity in the Injury and Infection Priming against Bacteria in Aedes aegypti Mosquitoes - Vargas, Valeria; Moreno-García, Miguel; Duarte-Elguea, Erika; Lanz-Mendoza, Humberto (Frontiers in Microbiology, 2016)
Injury and infection priming has been observed in several insect groups, reported as host immune protection against contact with a pathogen caused by a previous infection with the same. However, the specific response against a pathogen has not been demonstrated in all insect species. Investigating the specific priming response in insects is important because their immune strategies probably reflect particular selective pressures exerted by different pathogens. Here, we determined whether previous infection of Aedes aegypti would enhance survival and/or lead to greater and specific AMP expression after a second exposure to the same or a distinct bacterium. Mosquitoes previously immunized with a low dose of Escherichia coli, but not Staphylococcus aureus, showed increased survival. Although the host protection herein demonstrated was not specific, each bacterium elicited differential AMP expression. These results can be explained by the susceptible-primed-infected (SPI) epidemiological model, which poses that in the evolution of memory-like responses (priming), a pivotal role is played by pathogen virulence, associated host damage, and the host capacity of pathogen recognition.